Impact of Button Mushroom Stem Residue as a Functional Ingredient for Improving Nutritional Characteristics of Pizza Dough - Gallardo, Miguel A.; Vieira Júnior, Wagner G. [UNESP]; Martínez-Navarro, María Esther; Álvarez-Ortí, Manuel; Zied, Diego C. [UNESP]; Pardo, José E. (MDPI, 2024)
In this study, the formulation of doughs was investigated using varying percentages of Agaricus bisporus flour, with the aim of utilizing mushroom stem fragments, typically considered production waste. The stem residues were collected from a mushroom cultivation facility, cleaned, and washed to remove impurities. The material was then subjected to two different drying methods: conventional dehydration and freeze-drying. After drying, the material was ground to produce mushroom flour. Doughs were formulated with different proportions of this flour and analyzed for texture profile, color, nutritional value, phenolic content, antioxidant activity, and sensory characteristics. The inclusion of mushroom flour resulted in darker doughs, particularly when the flour was obtained through conventional dehydration due to oxidation processes. This substitution also affected texture parameters, leading to increased hardness and reduced elasticity in most treatments compared to the control sample. In addition, cohesiveness progressively decreased from 0.35 in the control to 0.14 in the sample made with 100% dehydrated flour and 0.20 in the sample made with 100% freeze-dried flour, resulting in brittle doughs. The most significant impact on nutritional value was an increase in protein, fat, and dietary fiber levels, reaching values over 5% of crude fiber in the sample to which 50% of dehydrated mushroom flour was added. Additionally, mushroom flours exhibited a high proportion of phenolic compounds, reaching values near 700 mg gallic acid/100 g in the flour from freeze-dried samples and 320 mg gallic acid/100 g in the flour from dehydrated samples. These values reflect a higher content of phenolic compounds in products made with mushroom flours and an increased antioxidant capacity compared to the control sample. Sensory evaluation showed that the texture remained unaffected; however, flavor perception was altered at a 50% mushroom flour substitution. In terms of external appearance, only the 25% freeze-dried mushroom flour formulation was statistically similar to the control, while all other treatments were rated lower.
Keywords: dough production; food enrichment; food reuse; mushroom residue; waste